Access to Heteroleptic Fluorido‐Cyanido Complexes with a Large Magnetic Anisotropy by Fluoride Abstraction. Issue 26 (15th April 2020) - Liu, Jun‐Liang; Pedersen, Kasper S.; Greer, Samuel M.; Oyarzabal, Itziar; Mondal, Abhishake; Hill, Stephen; Wilhelm, Fabrice; Rogalev, Andrei; Tressaud, Alain; Durand, Etienne; Long, Jeffrey R.; Clérac, Rodolphe
Abstract: Silicon‐mediated fluoride abstraction is demonstrated as a means of generating the first fluorido‐cyanido transition metal complexes. This new synthetic approach is exemplified by the synthesis and characterization of the heteroleptic complexes, trans ‐[M IV F4 (CN)2 ] 2− (M=Re, Os), obtained from their homoleptic [M IV F6 ] 2− parents. As shown by combined high‐field electron paramagnetic resonance spectroscopy and magnetization measurements, the partial substitution of fluoride by cyanide ligands leads to a marked increase in the magnetic anisotropy of trans ‐[ReF4 (CN)2 ] 2− as compared to [ReF6 ] 2−, reflecting the severe departure from an ideal octahedral (Oh point group) ligand field. This methodology paves the way toward the realization of new heteroleptic transition metal complexes that may be used as highly anisotropic building‐blocks for the design of high‐performance molecule‐based magnetic materials. Abstract : Two fluorido‐cyanido transition metal complexes, trans ‐[M IV F4 (CN)2 ] 2− (M=Re, Os), have been prepared by a synthetic approach relying on silicon‐mediated fluoride abstraction. A dramatic enhancement of the magnetic anisotropy for the Re IV complex, as compared to its [ReF6 ] 2− precursor, is demonstrated by the combined analysis of high‐field electron paramagnetic resonance spectroscopy and magnetization data.